Multidrug-Resistant Klebsiella pneumoniae Causing Severe Infections in the Neuro-ICU - Nadezhda K. Fursova; Evgenii I. Astashkin; Olga N. Ershova; Irina A. Aleksandrova; Ivan A. Savin; Tatiana S. Novikova; Galina N. Fedyukina; Angelina A. Kislichkina; Mikhail V. Fursov; Ekaterina S. Kuzina; Sergei F. Biketov; Ivan A. Dyatlov (MDPI AG, 2021)
The purpose of this study was the identification of genetic lineages and antimicrobial resistance (AMR) and virulence genes in Klebsiella pneumoniae isolates associated with severe infections in the neuro-ICU. Susceptibility to antimicrobials was determined using the Vitek-2 instrument. AMR and virulence genes, sequence types (STs), and capsular types were identified by PCR. Whole-genome sequencing was conducted on the Illumina MiSeq platform. It was shown that K. pneumoniae isolates of ST14K2, ST23K57, ST39K23, ST76K23, ST86K2, ST218K57, ST219KL125/114, ST268K20, and ST2674K47 caused severe systemic infections, including ST14K2, ST39K23, and ST268K20 that were associated with fatal incomes. Moreover, eight isolates of ST395K2 and ST307KL102/149/155 were associated with manifestations of vasculitis and microcirculation disorders. Another 12 K. pneumoniae isolates of ST395K2,KL39, ST307KL102/149/155, and ST147K14/64 were collected from patients without severe systemic infections. Major isolates (n = 38) were XDR and MDR. Beta-lactamase genes were identified: blaSHV (n = 41), blaCTX-M (n = 28), blaTEM (n = 21), blaOXA-48 (n = 21), blaNDM (n = 1), and blaKPC (n = 1). The prevalent virulence genes were wabG (n = 41), fimH (n = 41), allS (n = 41), and uge (n = 34), and rarer, detected only in the genomes of the isolates causing severe systemic infections-rmpA (n = 8), kfu (n = 6), iroN (n = 5), and iroD (n = 5) indicating high potential of the isolates for hypervirulence.